Increased odds of having the metabolic syndrome with greater fat‐free mass: counterintuitive results from the National Health and Nutrition Examination Survey database. Issue 1 (25th November 2021) - Lagacé, Jean‐Christophe; Marcotte‐Chenard, Alexis; Paquin, Jasmine; Tremblay, Dominic; Brochu, Martin; Dionne, Isabelle J.
Abstract: Background: It is well established that body composition influences metabolic health, but emerging data are conflicting with the largely purported idea that a large fat‐free mass (FFM) has a protective effect on health. A potential explanation for these discrepancies is the way FFM is represented. The first objective is to determine the association between the metabolic syndrome (MetS) and FFM when the latter was represented in three different ways: 1—absolute FFM; 2—relative to squared height (FFMi); and 3—relative to body weight (FFM%). The second objective is to assess the impact of FFM on the relative risk of having the MetS after taking fat mass, physical activity, and sociodemographic variables into account. Methods: A total of 5274 individuals from the National Health and Nutrition Examination Survey database were studied. Age‐specific and sex‐specific quartiles of the three representations of FFM were defined, and the prevalence of MetS was determined in each of them. Quartiles of FFMi (kg/m 2 ) were used to calculate the odds ratios of having the MetS independently of FM, physical activity levels, and sociodemographic variables. Results: The prevalence of MetS decreased with increasing quartiles of whole‐body FFM% (Q1: 40%; Q4: 10%) but grew with increasing quartiles of absolute FFM (Q1: 13%; Q4: 40%) and FFMi (Q1: 10%; Q4: 44%). Similar results were observed for appendicular and truncal FFM. The odds ratios of having the MetS, independently of fat mass, physical activity, and sociodemographic variables, were significantly greater in the fourth quartile of FFMi when compared with the first quartiles of each specific subgroup [Q4 vs. Q1: younger men: 4.16 (1.99–8.68); younger women: 5.74 (2.46–13.39); older men: 1.98 (1.22–3.22); older women: 2.88 (1.69–4.90); all P  ≤ 0.01]. Conclusions: These results support the notion that the representation of FFM significantly influences its association with MetS and that a larger FFM, whether absolute or relative to height, is associated with alterations in cardiometabolic health.